A comparative study on perceptual evaluations of sports shoe exterior colors in Taiwan. Issue 2 (22nd January 2014) - Shieh, Meng‐Dar; Yeh, Yu‐En
Abstract We investigated consumer psychology, perception, and aesthetics in relation to sports shoe colors in Taiwan. Semantic differential rating (three emotional adjective pairs) and preference rating questionnaires were distributed among 512 university students to investigate whether their responses to various sports shoe colors differed. The results show that black is one of the most popular colors for sports shoes. The participants preferred designs that incorporated white as the secondary color and disliked those that featured green as the main and secondary colors. In addition, designs incorporating black or red as the main color with a bright color as the secondary color were considered modern. Black and white designs were perceived to be more suited to formal occasions. Furthermore, when the area of the main color exceeded that of the secondary color, the participants perceived a strong sense of simplicity, unless the colors were blue and green. The participants preferred two‐color over one‐color designs, and three‐color designs had a higher correlation with participant preferences. Women required more time than men to evaluate a sample. The men typically examined the samples from a frontal angle, whereas the women focused on the sides of the sample. The scoring scale was polarized (e.g., highest score for modern was −10 and 10 for retro), rendering the values of the Pearson correlation coefficient analysis comparatively low, resulting in weak correlations between variables. However, the relative differences of these values retained referential value regarding objective quantification. © 2014 Wiley Periodicals, Inc. Col Res Appl, 40, 178–193, 2015